2021
DOI: 10.3389/fpls.2021.722000
|View full text |Cite
|
Sign up to set email alerts
|

An Insight Into the Effect of Organic Amendments on the Transpiration Efficiency of Wheat Plant in a Sodic Duplex Soil

Abstract: Transpiration efficiency, the shoot biomass produced per unit of transpired water, is generally considered to be a constant property for a given crop in a given environment. To determine whether deep-banded organic amendments affect the transpiration efficiency (TE) of wheat plants and to provide a possible explanation for any changes in the TE, two-column experiments were carried out under controlled environment conditions. A Sodosol soil with physically constrained subsoils and a well-structured Vertosol wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It is generally reported that the adequate application of fertilizers enhances water use efficiency by increasing the transpiration efficiency of the crop plants [80,81]. This in turn helps in optimizing crop yields with higher drought tolerance [82].…”
Section: Role Of Microbial Bioinoculants In Mitigating Postharvest Ch...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally reported that the adequate application of fertilizers enhances water use efficiency by increasing the transpiration efficiency of the crop plants [80,81]. This in turn helps in optimizing crop yields with higher drought tolerance [82].…”
Section: Role Of Microbial Bioinoculants In Mitigating Postharvest Ch...mentioning
confidence: 99%
“…In an attempt to maximize the yield, farmers increase the doses of N fertilizer, leading to high application rates [88]. Moreover, negative effects of excessive N application on potato growth and tuber yield have been demonstrated [81,88]. Low phosphorus (P) availability is a major limiting factor for potatoes while the residual and unavailable P in some soils is estimated to sustain crop yield for the next century [89].…”
Section: Role Of Microbial Bioinoculants In Mitigating Postharvest Ch...mentioning
confidence: 99%
See 1 more Smart Citation